Computational Intelligence International Joint Conference, IJCCI 2015 Lisbon, Portugal, November 12-14, 2015, Revised Selected Papers - Merelo, Juan Julián; Rosa, Agostinho; Cadenas, José M.; Correia, António Dourado; Madani, Kurosh; Ruano, António; Filipe, Joaquim (Studies in Computational Intelligence, 2017)
This book includes a selection of revised and extended versions of the best papers from the seventh International Joint Conference on Computational Intelligence (IJCCI 2015), held in Lisbon, Portugal, from 12 to 14 November 2015, which was composed of three co-located conferences: The International Conference on Evolutionary Computation Theory and Applications (ECTA), the International Conference on Fuzzy Computation Theory and Applications (FCTA), and the International Conference on Neural Computation Theory and Applications (NCTA). The book presents recent advances in scientific developments and applications in these three areas, reflecting the IJCCI's commitment to high quality standards.